Late-long-term potentiation magnitude, but not Aβ levels and amyloid pathology, is associated with behavioral performance in a rat knock-in model of Alzheimer disease - Yesiltepe, Metin; Yin, Tao; Tambini, Marc D.; Breuillaud, Lionel; Zehntner, Simone P.; D’Adamio, Luciano (Frontiers in Aging Neuroscience, 2022)
Sequential cleavage of Amyloid precursor protein by - and -secretases lead to A formation. The widely accepted pathogenic model states that these mutations cause AD via an increase in A formation and accumulation of A in Amyloid plaques. APP mutations cause early onset familial forms of Alzheimer's disease (FAD) in humans. We generated App‐Swedish (Apps) knock‐in rats, which carry a pathogenic APP mutation in the endogenous rat App gene. This mutation increases -secretase processing of APP leading to both augmented A production and facilitation of glutamate release in Apps/s rats, via a -secretase and APP‐dependent glutamate release mechanism. Here, we studied 11 to 14-month-old male and female Apps/s rats. To determine whether the Swedish App mutation leads to behavioral deficits, Apps/s knock-in rats were subjected to behavioral analysis using the IntelliCage platform, an automated behavioral testing system. This system allows behavioral assessment in socially housed animals reflecting a more natural, less stress-inducing environment and eliminates experimenter error and bias while increasing precision of measurements. Surprisingly, a spatial discrimination and flexibility task that can reveal deficits in higher order brain function showed that Apps/s females, but not Apps/s male rats, performed significantly worse than same sex controls. Moreover, female control rats performed significantly better than control and Apps/s male rats. The Swedish mutation causes a significant increase in A production in 14-month-old animals of both sexes. Yet, male and female Apps/s rats showed no evidence of AD‐related amyloid pathology. Finally, Apps/s rats did not show signs of significant neuroinflammation. Given that the APP Swedish mutation causes alterations in glutamate release, we analyzed Long-term potentiation (LTP), a long-lasting form of synaptic plasticity that is a cellular basis for learning and memory. Strikingly, LTP was significantly increased in Apps/s control females compared to both Apps/s sexes and control males. In conclusion, this study shows that behavioral performances are sex and App-genotype dependent. In addition, they correlate with LTP values and not A or AD-related pathology. These data, and the failures of anti-A therapies in humans, suggest that alternative pathways, such as those leading to LTP dysfunction, should be targeted for disease-modifying AD therapy.